Parenting Perspektif Al-Qur’an dan Relevansinya pada Zaman Revolusi Industri 4.0 - Zainul Huda, Muhammad Habib; Qalyubi, Syihabuddin (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
The purpose of this research is to find out how the Qur'anic perspective of parenting and its relevance to the current context. Parenting in this case, namely, what obligations must be carried out by parents to their children. This research is Qualitative research with Descriptive Analysis method. The data source is the Qur'an, of course also referring to other sources. The data analysis technique uses Fazlur Rahman's Doable Movement Theory, which includes First Movement and Doable Movement. From this research, it is found that there are several obligations that parents must do to their children. The conclusions of this study are: (1) The Qur'an, implicitly or explicitly, has provided solutions on how to educate children with Quranic Parenting. (2) Among the obligations of parents towards children in accordance with the Qur'an are: Praying for Children, calling with affectionate names, Providing Mauidzah Hasanah, Providing Uswatun Hasanah, and Providing Good Food. (3) The relevance of Quranic Parenting in the current context is: First, parents before marriage and after marriage should not stop praying for righteous children. Second, parents familiarize themselves with calling their children with soothing calls. Third, parents should not get tired of always giving advice to their children, especially advice on faith and Islam. Fourth, parents must also always give examples and examples to children in terms of goodness. Fifth, parents must provide halal and good clothing, shelter, and food to their children as much as possible.